AI-Assisted Tourism Communication Quality and Visit Intention toward Fragile-Reputation Destinations: The Sequential Mediating Role of Perceived Safety, Destination Trust, and Destination Image: Evidence from Syria (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study explains how AI-assisted tourism communication quality is associated with visit intention toward fragile-reputation destinations through a sequential perceptual pathway involving perceived safety, destination trust, and destination image. The research problem stems from the fact that fragile-reputation destinations, including Syria, do not merely face a promotional challenge; rather, they face difficulty in transforming their tourism and heritage resources into visit intention because potential tourists continue to associate such destinations with risk, uncertainty, and limited trust in available information. In this context, the availability of tourism content alone is insufficient unless communication is clear, realistic, credible, and capable of reducing ambiguity about destination visitability. A quantitative scenario-based design was adopted in the Syrian context, and data were collected from a final sample of 250 Arabic-speaking potential tourists. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings show that AI-assisted tourism communication quality was positively associated with perceived safety, which was positively associated with destination trust. Destination trust, in turn, was associated with a more positive destination image, which subsequently increased visit intention. The results also support a sequential indirect effect of communication quality on visit intention through perceived safety, destination trust, and destination image. The study concludes that the marketing value of artificial intelligence in fragile-reputation destinations does not lie in the technology itself, but in its ability to support clear and credible tourism communication that helps potential tourists reassess safety, build destination trust, form a more favorable destination image, and develop visit intention.
Keywords: AI-assisted tourism communication quality; visit intention; fragile-reputation destinations; perceived safety; destination trust; destination image; tourism in Syria.